Coping with Rhizopertha dominica: Navigating the Economic Consequences and Mitigation Strategies in Post-Harvest Wheat - Srivastava, Shraddha; Awasthi , Sangeeta (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present investigation was carried out within the confines of the Department of Zoology at Acharya Narendra Dev Nagar Nigam Mahila Mahavidyalaya in Kanpur, Uttar Pradesh, in the year 2023. The primary objective was to delve into the economic ramifications stemming from the feeding habits of Lesser grain borer, Rhizopertha dominica, on wheat the focus of to assessed the resultant damage and subsequent losses incurred during storage. Upon meticulous observation, it became evident that R. dominica exacted a substantial toll on the overall quality and quantity of the stored wheat, culminating in significant economic losses. The deleterious impact on the grains after 90 days of storage commencement, revealed a staggering 11.37% loss in weight. Within this context, the efficacy of powdered forms of Cinnamomum verum and Syzygium aromaticum as botanical pesticides was meticulously evaluated in countering the presence of R. dominica within post-harvested wheat. The judicious application of 15 grams of powder per 100 grams of wheat grains yielded noteworthy effectiveness in mitigating the ravages and consequential financial setbacks inflicted by R. dominica. Both C. verum and S. aromaticum powders played a pivotal role in curbing weight losses, achieving notable reductions of up to 8.7% and 7.9%, respectively. Remarkably, C. verum emerged as the more potent agent compared to S. aromaticum in this regard. The utilization of these powdered remedies demonstrates a formidable potential in pest management, particularly in addressing the challenges posed by R. dominica infestations in stored wheat. This intervention serves as a robust deterrent against incurring substantial economic losses.